2023
DOI: 10.1080/14686996.2023.2165871
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte 3D culture and bioprinting using peptide functionalized hyaluronan hydrogels

Abstract: Astrocytes play an important role in the central nervous system, contributing to the development of and maintenance of synapses, recycling of neurotransmitters, and the integrity and function of the blood–brain barrier. Astrocytes are also linked to the pathophysiology of various neurodegenerative diseases. Astrocyte function and organization are tightly regulated by interactions mediated by the extracellular matrix (ECM). Engineered hydrogels can mimic key aspects of the ECM and can allow for systematic studi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 35 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…We have previously demonstrated that cell adhesions motifs, such as the fibronectin and laminin derived peptides RGD and IKVAV, with terminal azide groups can be easily conjugated to the HA-BCN backbone, resulting in improved cell−hydrogel interactions. 8 Printability. Shear thinning hydrogels are attractive as bioinks for extrusion-based 3D bioprinting since this facilitates the dispensing procedure while allowing for printing with high shape fidelity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that cell adhesions motifs, such as the fibronectin and laminin derived peptides RGD and IKVAV, with terminal azide groups can be easily conjugated to the HA-BCN backbone, resulting in improved cell−hydrogel interactions. 8 Printability. Shear thinning hydrogels are attractive as bioinks for extrusion-based 3D bioprinting since this facilitates the dispensing procedure while allowing for printing with high shape fidelity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The rounded fibroblast morphology is likely a result of the lack of cell-adhesion motifs in the hydrogels. We have previously demonstrated that cell adhesions motifs, such as the fibronectin and laminin derived peptides RGD and IKVAV, with terminal azide groups can be easily conjugated to the HA-BCN backbone, resulting in improved cell–hydrogel interactions …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations